2021
DOI: 10.3389/fmed.2021.662340
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Prediction Models for Mechanically Ventilated Patients: Analyses of the MIMIC-III Database

Abstract: Background: Mechanically ventilated patients in the intensive care unit (ICU) have high mortality rates. There are multiple prediction scores, such as the Simplified Acute Physiology Score II (SAPS II), Oxford Acute Severity of Illness Score (OASIS), and Sequential Organ Failure Assessment (SOFA), widely used in the general ICU population. We aimed to establish prediction scores on mechanically ventilated patients with the combination of these disease severity scores and other features available on the first d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 20 publications
2
37
0
Order By: Relevance
“…Liu et al [39] demonstrated that the predictive performance of the XGBoost model superior to three other ML models, including LR, SVM, and random forest, for predicting mortality in patients with AKI. Zhu et al [40] found that the XGBoost model outperformed the KNN, LR, decision tree, random forest, and ANN models in prediction of hospital mortality for mechanically ventilated patients. Moreover, a metaanalysis revealed that XGBoost was more effective than LR and other ML algorisms, including ANN, SVM, and Bayesian network, in the prediction of AKI [41].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [39] demonstrated that the predictive performance of the XGBoost model superior to three other ML models, including LR, SVM, and random forest, for predicting mortality in patients with AKI. Zhu et al [40] found that the XGBoost model outperformed the KNN, LR, decision tree, random forest, and ANN models in prediction of hospital mortality for mechanically ventilated patients. Moreover, a metaanalysis revealed that XGBoost was more effective than LR and other ML algorisms, including ANN, SVM, and Bayesian network, in the prediction of AKI [41].…”
Section: Discussionmentioning
confidence: 99%
“…We selected a dataset of sepsis patients from the MIMIC-III database, where sepsis is divided into general sepsis, severe sepsis, and septic shock ( 27 , 28 ). Figure 1 shows the detailed processes of data collection and preprocessing of sepsis patients, including the identification of sepsis patients, data extraction, data cleaning, and feature selection.…”
Section: Methodsmentioning
confidence: 99%
“…Logistic regression is reported to perform well in [31][32][33][34]. Random forests, k-nearest neighbors, support vector machines, decision trees and ensemble learning are also used in [33,[35][36][37][38]. While traditional machine learning approaches have been the norm in the clinical domain for years, newer mortality prediction studies have adopted deep learning-based approaches [39][40][41][42][43][44].…”
Section: Related Workmentioning
confidence: 99%